2022
DOI: 10.1212/nxi.0000000000001147
|View full text |Cite
|
Sign up to set email alerts
|

Choroid Plexus Volume in Multiple Sclerosis vs Neuromyelitis Optica Spectrum Disorder

Abstract: Background and ObjectivesThe choroid plexus has been shown to play a crucial role in CNS inflammation. Previous studies found larger choroid plexus in multiple sclerosis (MS) compared with healthy controls. However, it is not clear whether the choroid plexus is similarly involved in MS and in neuromyelitis optica spectrum disorder (NMOSD). Thus, the aim of this study was to compare the choroid plexus volume in MS and NMOSD.MethodsIn this retrospective, cross-sectional study, patients were included by convenien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 34 publications
6
39
0
Order By: Relevance
“…This implies that plexus enlargement may occur early in the course of MS, which is also supported by recent study of Ricigliano et al which demonstrated enlarged choroid plexus even at presymtomatic stage of the disease. 12,25 Stability of plexus and its weak association with baseline lesion volume (as was also observed in a recent study by M€ uller et al 24 ) and with the volume and severity of new lesions implies that, at least in our cohort, increased plexus size relates to a pathogenesis that is discrete from acute inflammatory demyelination, supporting, therefore, the notion that different mechanisms are likely to be responsible for acute and smouldering inflammation. 1,2,15,26,27 The essential role of the choroid plexus in maintaining the blood-CSF barrier and modulation of inflammatory cells trafficking into the central nervous system has recently attracted the attention of MS researchers.…”
Section: Figure 6 Analysis Of Association Between Plexus Volume and C...supporting
confidence: 87%
See 2 more Smart Citations
“…This implies that plexus enlargement may occur early in the course of MS, which is also supported by recent study of Ricigliano et al which demonstrated enlarged choroid plexus even at presymtomatic stage of the disease. 12,25 Stability of plexus and its weak association with baseline lesion volume (as was also observed in a recent study by M€ uller et al 24 ) and with the volume and severity of new lesions implies that, at least in our cohort, increased plexus size relates to a pathogenesis that is discrete from acute inflammatory demyelination, supporting, therefore, the notion that different mechanisms are likely to be responsible for acute and smouldering inflammation. 1,2,15,26,27 The essential role of the choroid plexus in maintaining the blood-CSF barrier and modulation of inflammatory cells trafficking into the central nervous system has recently attracted the attention of MS researchers.…”
Section: Figure 6 Analysis Of Association Between Plexus Volume and C...supporting
confidence: 87%
“…Stability of plexus and its weak association with baseline lesion volume (as was also observed in a recent study by Müller et al 24 1,2,15,26,27 …”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Recently, choroid plexus (CP) volume has been suggested as a reliable marker of neuroinflammation in several neurological disorders, including MS10–12 and Alzheimer’s disease 13. These highly vascularised structures, which extend along the floor of the lateral ventricles and the roof of the third and fourth ventricles, play a key role in the homoeostasis of the blood–cerebrospinal fluid (CSF) barrier and immune regulation within the central nervous system (CNS) 14.…”
Section: Introductionmentioning
confidence: 99%
“…In vivo MRI studies demonstrated that, compared with healthy controls (HC), patients with adult MS had higher CP volume,10–12 which was significantly associated with relapse rate,10 11 the severity of clinical disability10 and number and volume of brain T2-hyperintense and gadolinium-enhancing WM lesions,10–12 especially in patients with a relapsing–remitting (RR) course 11…”
Section: Introductionmentioning
confidence: 99%